Integrated transcriptome and co-expression network analysis revealed the molecular mechanism of cold tolerance in japonica rice at booting stage - Wang, Jiaqi; Chen, Ning; Li, Jiaying; Li, Chengxin; Fu, Guanzheng; Liu, Fuying; Zhao, Hongqiang; Liu, Yingying; Jiang, Weihan; Xia, Tianyu; Chen, Jie; Liu, Hualong; et al. (Frontiers in Plant Science, 2025)
BackgroundCold stress during the booting stage severely reduces rice yield by impairing pollen development and seed-setting rates. To uncover the molecular basis of cold tolerance, we analyzed phenotypic and transcriptomic data from 14 japonica rice varieties under cold stress, combined with WGCNA.ResultsThe results demonstrated that cold stress significantly decreased yield traits, particularly seed-setting rate—a reliable cold tolerance indicator. Transcriptome analysis identified 6,240 and 7,996 DEGs in cold-tolerant and cold-sensitive varieties, respectively, with 1,875 core genes enriched in key pathways like plant hormone signaling and MAPK cascades.ConclusionWGCNA analysis identified a seed-setting rate-associated blue module, which contained 10 highly connected candidate genes and 20 core transcription factors potentially involved in cold tolerance. This study provides novel insights into the molecular mechanisms of cold tolerance in rice and offers valuable targets for molecular breeding of cold-resistant cultivars.